Not Profiting from Precarity: The Work of Nonprofit Service Delivery and the Creation of Precasiousness - Baines, Donna; Cunningham, Ian; Campey, John; Shields, John (Just Labour, 2014)
This paper examines the impact of precarity on the nonprofit service providing sector (NPSS). Using in depth qualitative interviews, recent empirically-based surveys of the Ontario nonprofit sector and key academic and grey literature, we explore the deeper meaning of precarity in this sector. We contend that the NPSS is a unique, and in many respects, an ideal location in which to explore the workings and impact of precarity. Looking at the nonprofit sector reveals that precarity operates at various levels, the: 1) nonprofit labour force; 2) organization structure and operation of nonprofit agencies; and, 3) clients and communities serviced by these nonprofit organizations. By observing the workings of precarity in this sector, precarity is revealed to be far more than an employment based phenomenon but also a force that negatively impacts organizational structures as well as vulnerable communities.